Review of retrospective dosimetry techniques for external ionising radiation exposures - Ainsbury, E. A.; Bakhanova, E.; Barquinero, J. F.; Brai, M.; Chumak, V.; Correcher, V.; Darroudi, F.; Fattibene, P.; Gruel, G.; Guclu, I.; Horn, S.; Jaworska, A.; et al. (Radiation protection dosimetry, 2011)
The current focus on networking and mutual assistance in the management of radiation accidents or incidents has demonstrated the importance of a joined-up approach in physical and biological dosimetry. To this end, the European Radiation Dosimetry Working Group 10 on 'Retrospective Dosimetry' has been set up by individuals from a wide range of disciplines across Europe. Here, established and emerging dosimetry methods are reviewed, which can be used immediately and retrospectively following external ionising radiation exposure. Endpoints and assays include dicentrics, translocations, premature chromosome condensation, micronuclei, somatic mutations, gene expression, electron paramagnetic resonance, thermoluminescence, optically stimulated luminescence, neutron activation, haematology, protein biomarkers and analytical dose reconstruction. Individual characteristics of these techniques, their limitations and potential for further development are reviewed, and their usefulness in specific exposure scenarios is discussed. Whilst no single technique fulfils the criteria of an ideal dosemeter, an integrated approach using multiple techniques tailored to the exposure scenario can cover most requirements.